2014
DOI: 10.1155/2014/568081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulfur Induced Stress on Oxidative Status and Antioxidative Machinery in Leaves ofAllium cepaL.

Abstract: A pot culture experiment was carried out to assess the effect of sulfur stress on growth, oxidative status, and antioxidative metabolism. Onion plants were treated with three different levels of sulfur, namely, 1.0, 4.0, and 8.0 mM S L−1. Plants raised with 4.0 mM S L−1 represent sufficient growth for the best vegetative yield. Plants supplied with 1.0 and 8.0 mM S L−1 showed retarded growth, chlorosis, and reduction in biomass and photoassimilatory pigments. Tissue sulfur concentration and cysteine were incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
12
0
2
Order By: Relevance
“…However, the optimum dose of sulfur causing a maximal change in growth differs from crop to crop. For example, sulfur application at the rate of 4 mM enhanced vegetative growth, while high concentration (8 mM) delayed the vegetative growth of onion plants 82 . Little information, however, exists until now on the effects of S-enriched humic acid application on crop productivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimum dose of sulfur causing a maximal change in growth differs from crop to crop. For example, sulfur application at the rate of 4 mM enhanced vegetative growth, while high concentration (8 mM) delayed the vegetative growth of onion plants 82 . Little information, however, exists until now on the effects of S-enriched humic acid application on crop productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress as well as S deprivation causes metabolic imbalance that leads to oxidative burst in plant cell 75 . S deficiency stimulates peroxidation of biomolecules due to excessive accumulation of reactive oxygen species (ROS) and reduced synthesis of S-containing compounds 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that low S stress decreased S-adenosyl-methionine (SAM) production leading to a reduction in chlorophyll content and an enhancement in photorespiration 19 . Moreover, S deficiency affects ribulose-1,5-bis-phosphate carboxylase/oxygenase (RuBisCO) activity and abundance of proteins involved in CO 2 assimilation, which ultimately decrease photosynthesis and biomass accumulation in plants 10 , 20 (Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic imbalance of S containing compounds generally leads to oxidative burst in plant cells 10 . The excessive accumulation of ROS due to S deficiency causes lipidperoxidation, damage to nucleic acids or proteins, and even cell death 21 (Figs 2 and 3 ) 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation